Surgery for Distant Melanoma Metastasis - Leung, Anna M. (2012)
Traditionally, distant metastatic melanoma has a poor prognosis due to lack of efficacious, FDA-approved systemic therapy and the limited use of surgical resection as a therapeutic option. More recently, new biologic therapies such as vemurafenib (Zelboraf) and ipilimumab (Yervoy) have showed strong promise and dramatically improved the landscape of stage IV melanoma therapy. Although there are numerous single-institution studies advocating the role for therapeutic surgical intervention, many remain skeptical of nonpalliative surgery for metastatic melanoma. Surgical resection of advanced melanoma has been proven to be effective as long as all disease is removed (R0). The combination of newer systemic therapies and surgical resection is currently under investigation. Understanding the tumor biology of melanoma and its mechanism of metastatic spread is essential to developing the most efficacious treatment strategy.